PENGGUNAAN MODEL DISKURSUS MULTY REPRECENTACY BERBANTUAN MEDIA KELUBANG TARIF UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Delfira Anggraeni Ciptaning Tiyas; Henry Suryo Bintoro; Jayanti Putri Purwaningrum (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the difference in the improvement of the mathematical problem-solving ability between students who utilized Discourse Multy Representation model with Kelubang Tarif media and students who applied the expository model. This study was a quasi-experimental study conducted at one of the elementary schools in Kudus. The population of the study were all four grade students in an elementary school in Kabupaten Kudus. The samples were two classes which were selected by using a purposive sampling technique. This study utilized a nonequivalent pretest-posttest control group design. The instrument of this study was a test in order to know the students' mathematical problem-solving abilities through descriptive quantitative analysis techniques. The data were tested by using N-Gain test. The results of this study showed that there was a difference in the improvement of the mathematical problem-solving ability between students who learned by implementing Discourse Multy Representation model with Kelubang Tarif media and students who accepted the expository model. Therefore, Discourse Multy Representation with Kelubang Tarif media could be utilized as the alternative of mathematic learning in order to improve students’ problem-solving ability